Ol’ga Frejdenberg, La trama di Tristano e Isotta sui mitologemi del segmento Egeo del Mar Mediterraneo (ENTHYMEMA, 2019)
Here it is presented the Italian translation of Syuzhet Tristana i Isolda v mifologemakh egeyskogo otrezka sredizemnomorya (1932) by Olga Mikhailovna Freydenberg. The essay is part of the work collection Tristan i Isolda. Ot geroini lyubvi feodalnoj Evropy do bogini matriarkhalnoj Afrevrazii and it was published by the Academy of Sciences of Leningrad.
Keywords: Tristan; Isolda; Freydenberg; Greece